An integrated simulation-optimization modeling system for water resources management under coupled impacts of climate and land use variabilities with priority in ecological protection. (August 2021) - Li, Congcong; Cai, Yanpeng; Tan, Qian; Wang, Xuan; Li, Chunhui; Liu, Qiang; Chen, Dongni
Abstract: An integrated simulation-optimization modeling system (ISOMS) approach was developed for assessing adaptive strategies in response to coupled impacts of climate and landuse variations. The ISOMS can not only reflect future hydrological trends under changing environment, but also provide water-allocation plans under various uncertainties expressed as random or fuzzy feature systematically. A case study of Anning River Basin with dry and warm characteristics in the upper Yangtze River was applied to inspect the model's applicability. A range of alternatives to adaptive strategies were generated under combinations of climate and landuse scenarios with different satisfaction levels. Results reveal that: (i) there exist increasing trend of temperature and precipitation in future period (2021–2050); (ii) the streamflow variation is more sensitive to climate change than landuse change; (iii) the hydrologic system uncertainties would lead to changes in water resources allocation; (iv) a low level of uncertainty satisfaction or a high level of violation risk would reduce the system reliability for the water resources system. The ISOMS approach has tremendous significance for evaluating hydrologic variations with complicated uncertainties, and providing optimal water allocation schemes responding to the coupled impacts of climate and landuse variations among society, economy and environment. Highlights: An integrated simulation-based optimization modeling on MIKE SHE and MFSCP method. A set of 31 GCMs and three CA-Markov modules for climate and land use projections. Hydrological process and water availability vary under changing conditions. Adaptive strategies for water resources generated under multiple scenarios.